EFFECTS OF PROFENOFOS AN ENDOCRINE DISRUPTING CHEMICAL ON LEYDIG’S CELLS IN RABBITS - S. A. Memon; S. A. Shaikh; N. Memon (Journal of Animal and Plant Sciences, 2014)
This study was conducted to know the toxic effects of organophosphate (Profenofos) pesticide an endocrine disruptor on leydig’s cells in rabbits. In this context, a total of 40 male rabbits, Oryctolagus cuniculus, were used as two test groups and one group labeled as control group.  One tenth of LD50 Profenofos 500 EC, was orally administrated in animals for 11 and 15 days. Decline in the body weight was highly significant (P < 0.001) in treated animals. At the termination of experimental studies animals dissected and testes were removed in order to evaluate the testicular weight and histological parameters. Weight of the testes in the experimental animals exposed to profenofos for eleven and fifteen days was decreased highly significant (3.05 ± 0.12 and 2.93±0.12 gms (P < 0.001) respectively as compared to 4.10 ± 0.12 gms. in the control group. Histopathological observations revealed that the leydig’s cells of the rabbits exposed to profenofos were totally vanished or regressed. Even the interstitial space became compressed and completely hypertrophied and tumor like mass was also seen in few seminiferous tubules. This indicates the intensity of the toxic effect of Profenofos. It is concluded that exposure of profenofos cause endocrine disruption and shown drastic effects on the testicular tissues in rabbits.
Keywords: Profenofos; Rabbits; Leydig’s cell; Endocrine disruptor